Health Literacy Level of Posyandu Cadres in Preventing Stunting Prevalence in Tambak Kalisogo Village - Rodiyah, Isnaini; Choiriyah, Ilmi Usrotin; Rustianingsih, Eni (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to analyze health literacy in village posyandu cadres in preventing stunting prevalence in Kalisogo Tambak Village. This research uses descriptive statistical methods with quantitative and qualitative approaches obtained and then used as analysis material. Data collection techniques are carried out by conducting observations, interviews, and questionnaires. The data analysis technique used is Likert scale measurement with the help of SPSS program version 26. The results of this study explain the analysis of 4 (four) aspects of health literacy which is elaborated with the prevention of stunting prevalence of village posyandu cadres which can be used as a reference to improve the ability of posyandu cadres in handling public health. Aspects according to Sorensen et.al. These include: 1) Access, 2) Understand, 3) Appraise and 4) Apply. Of the four indicators, the results of the health literacy index research on posyandu cadres in preventing stunting prevalence are the highest indicator in the dimension of accessing various health-related information obtained from several reliable sources with a value of 68%. Then, the lowest score is on the indicator assessing various health-related information with a value of 55%. These results show that the health literacy ability of posyandu cadres in preventing stunting prevalence in Kalisogo Tambak Village is quite good, but in the aspect of assessing various health-related information, especially in stunting prevention, it needs to be improved again considering that stunting greatly affects the quality of human resources.